Effects of low- to high-angle normal faults on sedimentary architectures in the Eocene Wenchang Formation, Enping Sag, Pearl River Mouth Basin, South China Sea. Issue 7 (2nd October 2016) - Liu, Q. H.; Zhu, H. T.; Shu, Y.; Zhu, X. M.; Yang, X. H.; Tan, M.; Chen, H. H.; Yang, S. F.
ABSTRACT: The effects of low- to high-angle (>30°) normal faults on sedimentary architectural units in the Eocene Wenchang Formation, Enping Sag, Pearl River Mouth Basin (PRMB), South China Sea were investigated utilising a high-quality 3D seismic data set and restored paleogeomorphology. It has been shown that sequence stratigraphic units and sedimentary architecture are significantly controlled by the low- to high-angle normal faults. The Wenchang Formation, a second-order sequence, can be subdivided into two para-second-sequences (the Lower and Upper Wenchang sequences, E2 W L and E2 W U ) and seven third-order sequences (from base to top: SQ1∼SQ7). The low-angle fault confined sequence architecture of the Wenchang Formation is mainly characterised by lateral stacking with the ratio of the vertical subsidence (V) to horizontal slip (H) being reduced from 1/2 for E2 W L to 1/6 for E2 W U . In contrast, the high-angle fault confined sequence is characterised by vertical stacking with the ratio of V/H close to 1 for sequences SQ1 to SQ7. In the 3D seismic area, the features of sediment-dispersal pattern were interpreted based on an integrated analysis of paleogeomorphology, seismic reflection characteristics, stratal thickness distribution and multiple attribute clustering. The results show that the large-scale fan delta, belt-shape lacustrine deposit and bird-foot braided delta systems mainly developed in the low-angle fault confined sequences, whereas small-scale fan delta, rhombus-shaped lacustrine deposit and lobe-shaped braided delta systems inherited tectono-sedimentary architectures in the high-angle fault confined sequences.